2018
DOI: 10.1111/vco.12436
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of urinary and serum level of chemokine (C‐C motif) ligand 2 as a potential biomarker in canine urothelial tumours

Abstract: Chemokine (C‐C motif) ligand 2 (CCL2) is a chemotactic cytokine recruiting monocytes, releasing growth factors and promoting adhesion in vascular endothelium. Elevated serum and urinary CCL2 levels and expression of its receptor (CCR2) have been associated with tumorigenesis in human urinary malignancies. CCL2 implication has not been investigated in canine urothelial carcinoma. The aim of this study was to evaluate CCL2 serum and urine levels (measured by ELISA) in dogs with urothelial carcinoma or non‐neopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 40 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…They found significantly higher concentrations of CCL2 in dogs affected with neoplasia than in healthy dogs. Other authors have observed significantly increased serum concentrations of CCL2 in dogs with pulmonary metastatic oral malignant melanoma (Maekawa et al 2022), urothelial carcinoma (Shimizu et al 2019), lymphoma (Perry et al 2011) and histiocytic sarcoma (Nielsen et al 2013). Allende et al (2020) reported an increased serum level of CCL2 in dogs with osteosarcoma; however, a significant difference was not found between the affected dogs and the healthy controls.…”
Section: Discussionmentioning
confidence: 92%
“…They found significantly higher concentrations of CCL2 in dogs affected with neoplasia than in healthy dogs. Other authors have observed significantly increased serum concentrations of CCL2 in dogs with pulmonary metastatic oral malignant melanoma (Maekawa et al 2022), urothelial carcinoma (Shimizu et al 2019), lymphoma (Perry et al 2011) and histiocytic sarcoma (Nielsen et al 2013). Allende et al (2020) reported an increased serum level of CCL2 in dogs with osteosarcoma; however, a significant difference was not found between the affected dogs and the healthy controls.…”
Section: Discussionmentioning
confidence: 92%
“…A previous study has shown that urine CCL2 concentration as a diagnostic biomarker for urothelial carcinoma shows a sensitivity of 95% and specificity of 38%. 40 The simultaneous analysis of urine CCL17, which has a relatively high specificity, and CCL2, which has high sensitivity, may serve as a more accurate biomarker for urothelial carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…of dogs with urothelial carcinoma [133]. The combined measurement of CCL17 and CCL2 in urine might improve the sensitivity and specificity of each biomarker for detection of canine urothelial cancer [131].…”
Section: Diagnosismentioning
confidence: 99%